1992
DOI: 10.3168/jds.s0022-0302(92)77968-5
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatographic Analysis of Volatile Sulfur Compounds from Heated Milk Using Static Headspace Sampling

Abstract: An investigation was conducted to test the feasibility of using gas chromatography with static headspace sampling as an objective tool to measure milk flavor quality. Heated milk off-flavor was chosen for study. Different strategies were tried for increasing the sensitivity of a commercially available headspace method, including salting out with sodium sulfate, cryofocusing during injection, and applying backpressure to the sampling loop. With the aid of a sulfur-specific detector, the resulting system was suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 13 publications
0
37
1
Order By: Relevance
“…It has been reported that sulfur compounds such as hydrogen sulfide, methanethiol, carbon disulfide, DMS, dimethyl disulfide and dimethyl trisulfide liberated by heat from the exposed sulfydryl groups of whey proteins, primarily b-lactoglobulin, are responsible for the cooked flavor of heated milk (Christensen & Reineccius, 1992;Patrick & Swaisgood, 1976;Simon & Hansen, 2001). Only DMS was detected in our study, probably owing to the mass spectrometric detectors or the SPME technique being insufficiently sensitive to allow the analysis of sulfur compounds at the low levels of concentration produced.…”
Section: Article In Presscontrasting
confidence: 68%
“…It has been reported that sulfur compounds such as hydrogen sulfide, methanethiol, carbon disulfide, DMS, dimethyl disulfide and dimethyl trisulfide liberated by heat from the exposed sulfydryl groups of whey proteins, primarily b-lactoglobulin, are responsible for the cooked flavor of heated milk (Christensen & Reineccius, 1992;Patrick & Swaisgood, 1976;Simon & Hansen, 2001). Only DMS was detected in our study, probably owing to the mass spectrometric detectors or the SPME technique being insufficiently sensitive to allow the analysis of sulfur compounds at the low levels of concentration produced.…”
Section: Article In Presscontrasting
confidence: 68%
“…It has been reported that the concentration of H 2 S in milk increases linearly with heating temperature (Christensen & Reineccius, 1992;Hutton & Patton, 1952). H 2 S is produced mainly from sulfydryl groups of sulfur-containing amino acids (cysteine) in b-lactoglobulin (Badings, Van der Pol, & Neeter, 1981;Damodaran, 1996).…”
Section: Resultsmentioning
confidence: 98%
“…The carrier gas was zerograde nitrogen, and the flow rate was 10 ml/min. The DMS concentration in the headspace gas was measured by isothermal (120°C) gas chromatography on a 30 m  0.25 mm DB-17 capillary column (J&W Scientific Inc., Folsom, CA) with a flame photometric detector operated in sulfur mode (Christensen & Reineccius 1992). Ultrahigh-purity helium was used as carrier gas at flow rate of 1.0 ml/min with a split ratio of 100:1.…”
Section: Methodsmentioning
confidence: 99%